Community renewable energy: Benefits and drivers. (December 2020) - Soeiro, Susana; Ferreira Dias, Marta
Abstract: The energy transition alone causes a physical and social transition in places and communities. Although Community Energy (CE) emerged as a grassroots innovation, which is of interest to citizens and policy makers, the benefits, drivers, and barriers need to be extensively studied. In this article we analyse, through a survey, the benefits and drivers that affect the creation and development of the CE. The results lead to two important insights: firstly, environmental benefits outweigh financial ones when creating and developing CE's. Secondly, it is important to mention the benefits that the CE bring to the regions where they are created. Third, when developing an CE, we must consider must be taken of the impacts it will have on the environment and the community where it will be installed.